Use of scenographic simulation to perform magnetic resonance imaging to reduce the indication of anesthesia in children - de Paula Silva Naziazene Lima, Geiza (Seven Editora, 2023)
Introduction: Health professionals who are specialists in performing MRI exams, note that there is a need for greater preparation of the team when the exam is performed with pediatric patients. Being observed in the patients of this age group greater anxiety, fear, curiosity and lack of understanding in the instructions necessary to perform the exam. The use of a simulator in the pre-examination can help the patient understand what will be done during the MRI examination and consequently, the use of sedation is not necessary in these patients. Objective: To analyze, from the perspective of nursing, the effectiveness of using scenographic simulation in magnetic resonance imaging exams to reduce the need for anesthesia in children, in order to expand its use in public hospitals in the Federal District. Materials and methods: A cross-sectional, retrospective, descriptive and observational study was carried out. With data collection directly from the medical records of selected research participants. The medical records of patients aged between 5 and 10 years old, who underwent the magnetic resonance exam from January 1, 2008 to December 30, 2019, were included. Results: 4,252 patients who met the inclusion criteria were included, of these, 53.3% were male and 46.7% female. The average age of the patients was 7.12 years and the fashion was 9 years (5-9 years). There was no need to use anesthesia in 97.4% of patients, it was used in 2.3% and there was no information in the medical records of 0.3% of patients. Conclusion: The use of the simulator - "scenographic resonance", in the desensitization of children to perform magnetic resonance imaging, proved to be an effective technique to perform this exam. Through this technique, with the proper training of nurses, it was possible to demonstrate the high success rate and the reduction of risks inherent to the anesthetic procedure, as well as the reduction of expenses related to this procedure. DOI: https://doi.org/10.56238/tfisdwv1-085